Annual Report - Vision Gaspé-Percé Now (2023)

Annual Report 2021-22 - Committee for Anglophone Social Action (CASA) (2022)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2022)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Annual Report - Vision Gaspé-Percé Now (2022)

Annual Report 2021 - Committee for Anglophone Social Action (CASA) (2021)

Rapport Annuel 2021 - Committee for Anglophone Social Action (CASA) (2021)

Annual Report 2019-2020 - Committee for Anglophone Social Action (CASA) (2020)

CAMI’s Annual General Meeting : 2019-2020 - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Annual Report - Vision Gaspé-Percé Now (2020)

Soutenir les enfants et les familles anglophones en Gaspésie et aux Îles-de-la-Madeleine - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings est une approche adaptée pour aider les enfants et les familles d’expression anglaise de la Gaspésie et des Îles-de-la-Madeleine. L’initiative est née d’une collaboration entre CASA, CAMI et VGPN, qui ont commencé à travailler avec des partenaires régionaux et locaux pour mieux adapter les programmes et les services afin de soutenir les enfants d’expression anglaise de 0 à 5 ans et leurs familles. Le Réseau communautaire de santé et de services sociaux (RCSSS) a adopté cette approche comme cadre de référence provinciale pour les communautés d’expression anglaise.

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings is an adapted approach to supporting English-speaking children and families in the Gaspé and Magdalen Islands. It originated through a collaboration between CASA, CAMI and VGPN who began to work with regional and local partners to better adapt programs and services to support English- speaking children 0 to 5 years old and their families. This approach has been adopted by the CHSSN as a provincial framework for English- speaking communities.

Annual Report 2018-2019 - Committee for Anglophone Social Action (CASA) (2019)

CAMI’s Annual General Meeting : 2018-2019 - Council for Anglophone Magdalen Islanders (CAMI) (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary; Maynard, Hugh; Burke, Helena; Brinklow, Laurie; Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2019)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Annual Report - Vision Gaspé-Percé Now (2019)

English-speaking Communities of the Gaspésie-Îles-de-la-Madeleine : A Regional Profile - Vision Gaspé-Percé Now (VGPN) (2018)

Regional Tourism Action Plan for the English-speaking Community of the Gaspé and Magdalen Islands 2018-2023 - Harrison, Kim (Committee for Anglophone Social Action (CASA), 2018)
The Committee for Anglophone Social Action (CASA) works to build and strengthen the vitality of the English-speaking community of the Gaspé Coast This regional tourism action plan has been developed to foster the increased participation in the tourism industry by English speakers and encourage a greater number of English speakers to visit the Gaspé Coast and the Magdalen Islands. The English-speaking community of the region faces many socio-economic challenges as compared to the francophone population. Increased participation in tourism industry would generate social and economic benefits at the individual, organizational and community level. A recent study commissioned by the Community Economic Development and Employability Committee has indicated a high level of interest by American and Ontarian travellers in visiting the attractions of the English-speaking Quebec, as well as the desire to receive English services when visiting the province.
Keywords: Official Language Minority Community (OLMC)

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

CAMI’s Annual General Meeting : 2017-2018 - Council for Anglophone Magdalen Islanders (CAMI) (2018)

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

Literature Review - Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2016)
Small, rural and remote regions around the world are transforming due to forces outside of their control such as globalization, neoliberalism and climate change. While often characterized as being in a state of decline due to dwindling populations and employment opportunities, this literature review reveals that numerous small communities are finding ways to capitalize on these forces of change. The review focuses on regions similar to the Magdalen Islands – situated in the western world, shaped by colonial powers, and relatively well off. The common pattern found among the successful cases is a development approach that is internally focused, builds on existing assets (human, physical and intangible) and is scale appropriate with results that are, therefore necessarily unique to each community. These cases all include senior government support, especially in the form of funding, and in some instances, capacity building, that allows community members to carry the torch and take up the work of revitalizing their community in the ways they deem appropriate.

Annual Report / Rapport annuel - Vision Gaspé-Percé Now (2016)

Profile communautaire jeunes et aînés : Populations anglophones Gaspé - Vision Gaspé-Percé Now (2016)
Ce document est une ressource pour les organismes communautaires et gouvernementaux et pour ceux qui peuvent bénéficier de l’information visant les aînés et les jeunes anglophones de Gaspé. La production du document est possible grâce au soutien financier de Santé Canada. Les données démographiques ont été fournies par le Réseau communautaire de santé et des services sociaux (RCSSS).

The Build - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2015)
This case study presents a project being implemented in the Baiedes-Chaleurs, Quebec, by which a group of elementary and high school students are building a sailboat with a teacher. They have the support of a broad range of community, institutional and non-for-profit partners who believe, like them, that a challenging project can have positive outcomes both inside and outside the classroom.

Îles-de-la-Madeleine : Portrait de la communauté d'expression anglaise - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
Le présent portrait a été réalisé en collaboration avec de nombreux partenaires locaux, à l’initiative du Conseil des anglophones madelinots (CAMI) et avec l’appui du Réseau communautaire de santé et de services sociaux (RCSSS). Parmi les autres groupes ayant participé au processus figurent la Municipalité de Grosse-Île, l’école de Grosse-Île, la Corporation d’employabilité et de développement économique communautaire (CEDEC), le Centre scolaire communautaire (CSC) et l’Agglomération des Îles (comité de développement social/Les Îles en Forme).

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme).

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme). The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of the Magdalen Islands in order to create a community development plan that addresses the issues it faces.

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

Our Story : The New Carlisle Community Learning Centre Developmental Evaluation Report - Chatterton, Tammy; Legault, Emma (Leading English Education and Resource Network (LEARN), 2014)
The New Carlisle Community Learning Centre (NCHS CLC) is one of 37 community schools in Quebec. We are located in a small town on the Gaspesian Peninsula. Many people refer to the location as The Baie Des Chaleur. Our vibrant CLC is located in the town of New Carlisle, within New Carlisle High School. The centre was established to encourage lifelong learning by facilitating access to services and offering support to families, students and community members. The founders believed that a CLC would bridge the noticeable gaps in rural communities like ours, balancing the playing field so that our community would have the same opportunities as more fortunate and larger areas. Therefore, the CLC’s main goal is to link partners together to create a culture of lifelong learning that enhances the capacity of the population to live in healthy vibrant communities.

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Rapport Annuel 2009-2010 - Leading English Education and Resource Network (LEARN) (2010)
Dans une province aussi vaste que le Québec, où les écoles et les commissions scolaires sont dispersées sur une immense étendue géographique, la notion de rassembler les gens pour en faire une COMMUNAUTÉ de collaboration semble un obstacle gigantesque, sinon insurmontable. Dans la réalité, les gens partagent des intérêts similaires et des objectifs communs et cette notion d’impossibilité physique s’estompe rapidement. Cette évolution est particulièrement vraie quand l’objectif ultime est la réussite scolaire de nos enfants au niveau des écoles élémentaires et secondaires. LEARN a pour objectif de servir de catalyseur et de facilitateur pour la création de communautés de collaboration réunissant les éducateurs, les parents et les élèves à l’échelle de la province. L’objectif de notre organisation est de déployer tous les efforts possibles pour réunir les forces positives du milieu éducatif anglophone afi n de contribuer au partage des connaissances et des expériences disponibles au sein de notre communauté.

Grandma's Kitchen Table : Tips, Resources and Recipes - Council for Anglophone Magdalen Islanders (CAMI)

Partnering to Meet the Growing Needs of English-Speaking Seniors During the Pandemic - Council for Anglophone Magdalen Islanders (CAMI)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of The Magdalen Islands - Council for Anglophone Magdalen Islanders (CAMI)